Investigation of magnetic, mechanical and flame retardant properties of polymeric nanocomposites: Green synthesis of MgFe2O4 by lime and orange extracts. (1st November 2019) - Joulaei, Marjan; Hedayati, Kambiz; Ghanbari, Davood
Abstract: A wide range of toxic flame retardants have been synthesized while most of them have environmental challenges. In this study, magnesium ferrite nanoparticles are introduced as a new type of nontoxic and effective inhibitors against fire. MgFe2 O4 nanostructures were synthesized via a sol-gel green auto-combustion method using fruit extracts such as orange, grapefruit and lime. Magnesium ferrite was added to sodium carboxymethyl cellulose (CMC), polystyrene (PS) and acrylonitrile-butadiene-styrene (ABS) polymers. Results illustrate the flame stability of the CMC, PS and ABS were improved. Magnetic nanoparticles stick together and like an obstacle layer slow volatilization and preclude flame (oxygen) reaching to the sample (also show resistance to droplets falling). Improving mechanical stability was also examined; the insertion of magnesium ferrite nanoparticles to PS and ABS polymers increased their tensile strength. Graphical abstract: Image 1